2005
DOI: 10.1177/1476750305047983
|View full text |Cite
|
Sign up to set email alerts
|

An understanding of poverty from those who are poor

Abstract: A B S T R A C TParticipatory research in the study of poverty invites those living in difficult circumstances to participate in an analysis of their own livelihood situation. A participatory poverty assessment was facilitated with a small group of women who are members of a food co-operative in Niagara Falls, Canada and who live in poverty. The women explored together issues of well-being, the stress of living in poverty, the role of the social assistance system in shaping their lives and community attitudes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 12 publications
(11 reference statements)
4
38
0
1
Order By: Relevance
“…Bureaucratic red tape was sometimes interpreted as conveying mistrust. Participants also identified government policies that led to income-support cuts and expressed strong disapproval of the political parties (and their leaders) responsible for such policies because of their impact on meeting even basic needs: Overall, most low-income people viewed the help provided from government agencies as impersonal, reluctantly provided, and nonsupportive, which supports other research findings (e.g., Collins, 2005;Kerr, Frost, & Bignell, 2004;Reid, 2004).…”
Section: Sources Of Stigma Consciousnesssupporting
confidence: 56%
See 2 more Smart Citations
“…Bureaucratic red tape was sometimes interpreted as conveying mistrust. Participants also identified government policies that led to income-support cuts and expressed strong disapproval of the political parties (and their leaders) responsible for such policies because of their impact on meeting even basic needs: Overall, most low-income people viewed the help provided from government agencies as impersonal, reluctantly provided, and nonsupportive, which supports other research findings (e.g., Collins, 2005;Kerr, Frost, & Bignell, 2004;Reid, 2004).…”
Section: Sources Of Stigma Consciousnesssupporting
confidence: 56%
“…These strategies might be viewed as ways to counteract the moral exclusion that is perceived to be at the root of their social identities. Nevertheless, as in other studies (e.g., Collins, 2005;Nelson, 2002;Reid, 2004), participants also reported feelings of shame that suggest an internalization of the stereotypes they wish to refute. Feelings of shame necessitated strategies such as self-isolating and concealing poverty to preserve self-esteem, gain acceptance, and reduce fear of stigmatization.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Previous research has shown that social benefit recipients and people living in poverty often perceive negative judgements and feel degraded, isolated, devalued, blamed and looked down upon [1117]. We found that over 18% of the general Dutch population perceived some kind of SEP-related stigmatisation, and that people in the lowest income and occupational groups were significantly more likely to perceive stigmatisation (respectively, 22.0% and 27.5%) [18].…”
Section: Introductionmentioning
confidence: 63%
“…En este sentido, cobra relevancia el problema del reconocimiento social. El lenguaje que construyen no se asienta sobre un discurso de derechos, que dé cuenta de tipos de situaciones similares a las reveladas por investigaciones sobre beneficiarios de ayudas sociales en las sociedades francesa y estadounidense (Baker, 2005;Murard, 2002). La inscripción dentro de un discurso de derechos supone un soporte identitario que se vincula con una visión universalista asentada sobre la condición ciudadana del sujeto.…”
Section: Características Del Territorio Y Los Sujetos De Estudiounclassified